The structural development of Istisna' sukuk structure from Shari'ah perspective - Adam Sa'ad, Auwal; Mohammad Deen, Mohd Napiah; Ibrahim, Uzaimah (International Institute of Advanced Islamic Studies (IAIS), 2016)
Istiṣna’ sukuk structures have been widely accepted for manufacturing and construction financing purposes. This paper looks at the structural development of Istiṣna’ Sukuk and evaluates both its basic and combination structures. Concerning the former, the paper argues that when Istiṣna’ is used for asset purchasing exercises, it should strictly comply with the general Shari’ah rules regarding Istiṣna’ contracts. Prices must therefore be stipulated at the beginning, as must quality and expected delivery times. The paper then highlights some conflicting features arising from the combination of Istiṣna’ and Ijarah transactions. These raise Shari’ah issues when the issuer seeks to lease an asset to the end user at maturity, even though the asset has been transferred to that end user by way of the Istiṣna’ contract. It is therefore recommended that the market innovates in order to develop additional structures free from this type of impediment. The study proposes a multiple contract’ structure be used whenever Istiṣna’ sukuk is issued in combination with other debt and equity instruments. This will help overcome Shari’ah issues related to secondary markets in Istisna' sukuk issuances.